Combined Resections with Colorectal Surgeries and Their Combined Natural Orifice Specimen Extractions (NOSE): A Clinical Practice Review - Aydin, Mehmet Can; Saglam, Kutay (AME Publishing Company, 2023)
Compared to conventional ones, minimally invasive surgical techniques have come to the fore in many fields, especially in colorectal surgery (CRS), due to their benefits. These benefits are better postoperative outcomes, particularly due to less abdominal trauma and smaller incisions. However, postoperative pain, incisional hernia or infection, and poor cosmesis, due to abdominal incisions made for specimen extraction, reduce the positive results that can be achieved. The basic starting point of natural orifice specimen extraction (NOSE) surgery is to eliminate these incisions and their negative effects. NOSE has been performed more frequently, especially in CRS, with the increase in experience. In some of the patients, in addition to CRS, combined resections may be required for metastases, secondary primary malignancies, or benign diseases. However, in the literature, NOSE in combined resections with CRS is limited to case reports and it is controversial. We aimed to review the literature in terms of NOSE for combined resections with CRS, including preoperative details, technical feasibility, perioperative findings and postoperative results. When a total of 42 cases in the literature were examined; it was observed that organs such as liver, stomach, pancreas, gallbladder, endometrium and ovaries were removed synchronously in CRS combined with NOSE. No major complication due to NOSE was observed perioperatively. According to these available data, NOSE in combined organ resections with CRS may be a safe and effective alternative surgical technique. It is obvious that there is a need for studies on this subject in order to obtain more reliable results.
Sağlam, Kutay/0000-0002-0919-8370;
Keywords: Natural Orifice Specimen Extraction (NOSE); Colorectal Surgery (CRS); Multivisceral; Synchronous; Simultaneous